Development of cation-directed acylation reactions - Rahemtulla, B (2018)
This thesis describes work conducted towards the enantioselective acylation of ketones using phase-transfer catalysis. Chapter 1 introduces the field of ketone acylation, with a focus on catalytic methods accompanied by the generation of axes, planes or points of chirality during these transformations. Chapters 2 describes the synthesis and evaluation of a variety of different frameworks for enantioselective ketone O-acylation; we highlight the selectivity and reactivity challenges faced when attempting this transformation (Scheme I). Chapter 3 focuses on the intramolecular O-acylation of enolates to generate axially chiral lactones. The development of these systems led to the discovery that the C/O-selectivity of this reaction was dependent on the steric hindrance about the axis of rotation, and C-acylation could be favoured under the correct conditions. Chapter 4 describes the conception and development of an enantioselective C-acylation reaction, culminating in the first reported catalytic enantioselective direct C-acylation of a ketone (Scheme II). The scope and limitations of this methodology were investigated and the products were successfully elaborated to afford a range of spirocyclic architectures. Finally, chapter 5 focuses on the kinetic analysis of the enantioselective C-acylation reaction in order to increase our understanding of the mechanisms behind phase-transfer catalysis and the mode of activation of the catalyst.